Syndrome of increased epithelial permeability, non-alcoholic fatty liver disease and cardiovascular diseases: what is the association and what ﻿can be done about it? - Natalia M. Vorobyeva; Olga N. Tkacheva (LLC "MEDIAFORMAT", 2021)
Syndrome of increased epithelial permeability occurs due to a decrease in the barrier function of the gastrointestinal mucosa due to impaired intercellular interactions, resulting in bacterial translocation (i. e. penetration of bacteria and toxins from the gastrointestinal lumen into the bloodstream), which can initiate an inflammatory process in various diseases. Syndrome of increased epithelial permeability plays an important role in the pathogenesis of many chronic diseases, including cardiovascular and non-alcoholic fatty liver disease (NAFLD). In turn, the presence of NAFLD is associated with an increase in cardiovascular morbidity and mortality. The use of ursodeoxycholic acid in NAFLD allows reducing both hepatological and cardiovascular risks. Gastro- and enteroprotector rebamipide not only eliminates increased epithelial permeability and acts at all three levels of protection of the mucosepithelial barrier, but also has multiple pleiotropic effects, which opens up wide prospects for its use in cardiovascular diseases and NAFLD. The hepatoprotective and anti-sclerotic effects of rebamipide identified in experimental studies need further study in clinical trials in NAFLD patients.